Pewarisan Sifat Karakter Kualitatif dan Kuantitatif pada Hipokotil dan Kotiledon Cabai (Capsicum annuum L.) - Rtionga, Arya Widura; Syukur, Muhamad; Yunianti, Rahmi; Sobir, dan (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
Characters on hypocotyl dan cotyledon are very potential used for effective and efficient morphology marker for some crop plants. However, the information about the inheritance of qualitative and quantitative characters on hypocotyl and cotyledon of chili pepper was not available. The aim of this research was to determine the inheritance of qualitative and quantitative characters on hypocotyl and cotyledon of chili pepper. This research used purple chili pepper (P1 (IPB C20)), green chili pepper (P2 (IPB C2)), F1, F1R, BCP1, BCP2, and F2 populations. Analysis for qualitative characters used mendelian genetics analysis, whereas model genetic prediction for quantitative characters used join scaling test analysis. The result showed that hypocotyl and cotyledon color of chili pepper controlled by single gene. The gene controlling purple color was dominant than the gene controlling green color on hypocotyl, whereas  the gene controlling green color was dominant than the gene controlling purple color on cotyledon. The additive-dominant genetic model with influence of additive-additive and additive-dominant interaction was suitable for hypocotyl length. The additive-dominant genetic model with influence of additive-dominant and dominant-dominant interaction was suitable for hypocotyls diameter. The additive-dominant genetic model with influence of additive-additive and dominant-dominant interaction was suitable for cotyledon width and cotyledon length.  Keywords: genetic model, morfology marker, natural cross-pollination